2017
DOI: 10.1007/s00530-017-0565-6
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and secure VoIP communication system with chaotic mapping and message digest

Abstract: As one of the most popular real-time services on the Internet, Voice over Internet Protocol (VoIP) has attracted researchers' attention in the information security field for its characters of real-time and high flow. To protect data security, a new covert VoIP communications system was proposed in this study to realize secure communications by hiding secret information in VoIP streams. In the proposed algorithm, secret data were divided into blocks after being encrypted with a block cipher, and then each block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As a new cryptographic theory, chaotic cryptography has been paid more and more attention by many cryptographers. Chaotic cryptography is widely used in image encryption [18][19][20][21][22], secure communication [23][24][25][26][27], neural network, and economics. However, a few scholars have tried to introduce chaotic systems into the field of lightweight encryption [28,29], and no one has tried to apply chaotic systems to lightweight stream ciphers.…”
Section: Introductionmentioning
confidence: 99%
“…As a new cryptographic theory, chaotic cryptography has been paid more and more attention by many cryptographers. Chaotic cryptography is widely used in image encryption [18][19][20][21][22], secure communication [23][24][25][26][27], neural network, and economics. However, a few scholars have tried to introduce chaotic systems into the field of lightweight encryption [28,29], and no one has tried to apply chaotic systems to lightweight stream ciphers.…”
Section: Introductionmentioning
confidence: 99%
“…J i a n g and T a n g [19] in 2017 have proposed a method to embed the secret message using chaotic maps and message digest. Message digest was employed to encrypt the secret data using block cipher technique, which is then embedded in the voice packets using chaotic maps.…”
Section: Least Significant Bit (Lsb) Modification Methodsmentioning
confidence: 99%
“…It is well known that the chaotic system has the characteristics of sensitivity of initial value and complexity of trajectory, so chaos has great potential application in many engineering fields, such as weak signal detection, [1][2][3][4] random number generator, [5,6] secure communication, [7][8][9][10][11][12][13] and image encryption. [14][15][16][17][18][19][20] Furthermore, Lin et al [21,22] studied the influence of electromagnetic radiation on the chaotic characteristics of neural networks, and found that appropriate electromagnetic radiation is helpful to treat some neurological diseases.…”
Section: Introductionmentioning
confidence: 99%